Evidências na COVID-19: atenção primária, telessaúde e atenção hospitalar - Christiane Corrêa Rodrigues Cimini (2022)
Introduction: The COVID-19 pandemic represents a major challenge for health systems around the world, with unprecedented demands on all levels of health care. In primary care, in addition to the care of individuals with flu-like symptoms, the discontinuity of monitoring patients with chronic diseases is a cause of great concern. In hospital care, the immediate need to assist patients with severe and critical forms of COVID-19 required the expansion of conventional and intensive care beds, technological resources for advanced life support and training in record time, as knowledge about the disease evolved. Objectives: The present study has two main objectives. Objective 1: To assess the impact of the COVID-19 pandemic on a cohort of people with hypertension and diabetes in primary care, and to develop and implement a digital solution to improve home monitoring. Objective 2: To assess whether the ABC2-SPH risk score can predict the need for invasive mechanical ventilation (IMV) in patients with COVID-19 and to compare its performance with other scores developed to predict IMV, mortality and other outcomes, including in non-COVID patients. Methods: To achieve objective 1: A multi-methodological study was developed. A quasi-experimental evaluation analyzed the impact of the pandemic on the frequency of consultations and control of patients with hypertension and diabetes in 34 primary health care centers (PHCC) in 10 municipalities in Mucuri Valley (Vale do Mucuri), Minas Gerais, between June 2017 and December 2020, considering March 14, 2020, as the cut-off point, when social restriction measures began. Then, a feasibility study developed an application with a decision support system (DSS) for community health workers (CHW) to identify, during home visits, patients with uncontrolled hypertension and/or diabetes and refer them for in person consultation at the PHCC. A panel of experts evaluated the app's feasibility, usability and usefulness through a specific questionnaire. To achieve objective 2: Retrospective cohort study, derived from the study originally called “Evaluation of the laboratory, radiological and symptomatologic profile of patients infected with the new coronavirus 2019 (SARS-CoV-2) in hospitals in the state of Minas Gerais”, which became a multicenter study, carried out in 31 hospitals, in 17 cities in five states The study included patients who were hospitalized in two periods: March to September 2020 and March to December 2021, with a confirmed diagnosis of COVID-19 . In this study, the ABC2-SPH risk score, developed to predict in-hospital mortality from COVID-19, was evaluated for the possibility of predicting the need for mechanical ventilation and compared to other scores: CALL, PREDI-CO, SUM, STSS, COVID_IRS_NLR, CURB-65, SOFA and 4C Mortality Score Results: Objective 1: Of 5070 patients, 4810 (94.9%) had hypertension, 1371 (27.4%) had DM, and 1111 (23.1%) had both diseases. There was a significant reduction in the weekly number of consultations (107, IQR 60.0-153.0 before vs 20.0, IQR 7.0-29.0) after social restriction; P<.001. Only 15.2% (772/5070) of all patients returned for a consultation during the pandemic. Individuals with hypertension had lower systolic (120.0, IQR 120.0-140.0 mm Hg) and diastolic (80.0, IQR 80.0-80.0 mmHg) blood pressure than those who did not return (130.0, IQR 120.0-140.0 mm Hg) and (80.0, IQR 80.0-90.0 mm Hg; P<.001). Also, those who returned had a higher proportion of controlled hypertension (64.3% vs 52.8%). For DM, there were no differences in glycohemoglobin levels. Concerning the DSS, the experts agreed that the CHWs can easily incorporate it into their routines and the app can identify patients at risk and improve treatment. Objective 2: Throughout the study, 4831 patients were included, median age 59.0 (IQR 48.0, 70.0) years-old and 46.3% female. Of those, 34.2 % required intensive care treatment, 26.6% required IMV and 18.7% died. Patients who required IMV had higher prevalence of hypertension, diabetes, obesity, and mortality when compared to those who did not require it (64.3% vs 2.3%, p<0.001). Based on the imputed dataset, the ABC2-SPH AUROC was 0.677 (95% CI 0.681-0.694). Considering only complete cases, the AUROC was 0.70, having the best performance among scores that had larger samples of complete cases. When the data were imputed, was 0.67. Considering only complete cases, the AUROC was 0.70 (95% CI 0.68-0.72, having the best performance among scores that had larger samples of complete cases. Overall, the score discriminations ranged from poor to fair. The SOFA Score had the highest sensitivity, 0.84 (95% CI 0.81-0.86). Conclusions: The COVID-19 pandemic caused a significant drop in the number of consultations of patients with hypertension and diabetes in primary care. An SSD for CHW proved to be feasible and useful for identifying uncontrolled patients at home. ABC2-SPH demonstrated better performance than the other scores, but not accurately enough to reliably predict the need for IMV COVID-19 hospitalized patients. Research should continue to develop easy-to-use scores with better calibration and discrimination, given the importance of assisting clinicians in decision-making when initiating advanced ventilatory support.